Histopathological pattern of endometrium in abnormal uterine bleeding of perimenopausal women - Talukdar, Bharat; Goswami, Rashmi Rekha; Mahela, Sangita; Ahmed, Noor Islam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of the study was to evaluate the histopathological pattern of endometrium in perimenopausal women presenting with abnormal uterine bleeding. Methods: This prospective study was carried out from June 2014 to May 2015 in a tertiary care teaching hospital on 180 number of perimenopausal women who presented with abnormal uterine bleeding. Results: Most of the patients were between 40-45 years of age (63.89%) and menorrhagia was the dominant clinical presentation 80 (44.44%). The commonest pathology was hyperplasia in 83 (46.11%) women with simple hyperplasia without atypia being the predominant pattern (65 cases) which was most commonly seen between 40 and 45 years of age. Atrophic endometrium was the common pattern in age group of ˃ 50 years. Other pathology identified were proliferative endometrium (20.56%), secretory endometrium (16.11%), endometritis (2.22%), endometrial polyp (2.22%), pregnancy related (2.22%) and carcinoma (1.11%). Conclusions: Histopathological pattern of the endometrium in abnormal uterine bleeding in perimenopausal women should be studied especially to rule out preneoplasia and malignancy.